EVALUATING THE EFFICACY OF CONTROLLED EXTENSIVE READING TASKS ON ESL LEARNING OUTCOMES - Mudogo, Benard Angatia; Barasa, David; Matseshe, James (LLT Journal: A Journal on Language and Language Teaching, 2023)
This study sought to establish whether students who are exposed to Controlled Extensive Reading Tasks (CERTs) will have higher learning outcomes during English as a Second Language (ESL) lessons. A 3-month intervention pilot of Controlled Extensive Reading (CER) instruction, was implemented in two secondary schools in Kakamega County, Western Kenya, from February to May 2023. We compared the impacts of the CERTs treatment group in ESL lessons in the pilot school with those of the control group that did not use the intervention but utilized the same instructional components. The findings revealed that assignment to the CERTs pilot group had additional improvement in the target language skills while the control group had somewhat constant learning outcomes. The study is useful to curriculum stakeholders who should consider such results alongside existing implementation strategies in ESL policies and program designs.